Pseudo-nitzschia Challenged with Co-occurring Viral Communities Display Diverse Infection Phenotypes - Carlson, Michael C. G.; McCary, Nicolette D.; Leach, Terence S.; Rocap, Gabrielle (Frontiers in Microbiology, 2016)
Viruses are catalysts of biogeochemical cycling, architects of microbial community structure, and terminators of phytoplankton blooms. Viral lysis of diatoms, a key group of eukaryotic phytoplankton, has the potential to impact carbon export and marine food webs. However, the impact of viruses on diatom abundance and community composition is unknown. Diatom-virus dynamics were explored by sampling every month at 2 coastal and estuarine locations in Washington state, USA resulting in 41 new isolates of the pennate diatom Pseudo-nitzschia and 20 environmental virus samples. We conducted a total of 820 pair-wise crosses of the Pseudo-nitzschia isolates and viral communities. Viral communities infected Pseudo-nitzschia isolates in 8% of the crosses overall and 16% of crosses when the host and viral communities were isolated from the same sample. Isolates ranged in their permissivity to infection with some isolates not infected by any viral samples and others infected by up to 10 viral communities. Isolates that were infected by the most viral communities also had the highest maximum observed viral titers (as high as 16000 infectious units ml-1). Titers of the viral communities were host dependent, as titers for one viral sample on 8 different hosts spanned 4 orders of magnitude. Sequencing of the Pseudo-nitzschia Internal Transcribed Spacer 1 (ITS1) of the revealed multiple subgroups of hosts with 100% ITS1 identity that were infected by different viral communities. Indeed, we repeatedly isolated groups of isolates with identical ITS1 sequences from the same water sample that displayed different viral infection phenotypes.  The interactions between Pseudo-nitzschia and the viral communities highlight the diversity of diatoms and emphasize the complexity and variability of diatom-virus dynamics in the ocean.